Surgical management of a case of recurrent carcinoma cervix: a case report - Kalpana, B.; Balamurugan, S. G.; Panda, Soumya Ranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Worldwide cervical cancer is the fourth most common cancers among females. Pelvic recurrence, distant metastases, or a combination of both can occur in patients of carcinoma cervix. A 42-year-old P2L2 with a history of carcinoma cervix stage 3-b came to our OPD for routine follow up. Two year back she was managed with chemoradiation for her primary carcinoma which had parametrium extension. There was a 1 × 1 cm lesion on the anterior vaginal wall which was diagnosed to be cervical recurrence. Patient underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy with pelvic lymphadenectomy. Patient is disease free till now. Treatment decisions should be individualised based on the performance status of the patient, the site of recurrence and/or metastases, the extent of metastatic disease, and prior treatment.